STUDY ON THE ESSENTIAL OIL AND TRANS –ANETHOL OBTAINED FROM SUMMER VIETNAMESE ANISE STAR - Tu, Nguyen Thi Minh; Hori, Natsuko; Trung, Vu Thanh; sawamura, Masayoshi; Thiem, Pham Van (Vietnam Journal of Science and Technology, 2012)
ABSTRACT Summer anise star collected from Lang Son in 2008 was studied. The material was characterized by the essential oil content of 8,75%, moisture content of 13,2%, acid index of 4.5 mg KOH/g, ester index of 254.17 mg KOH/g and the relative density of 0,981. The procedures of essential oil distillation and trans-anethol isolation have been studied based on the properties of anise material. The yield of proposed procedure reached 76,4 % and the purity of anethol isolated was 96,83%.